MARKETING STRATEGY OF AKASA SPECIALTY COFFEE AS A TOURIST ATTRACTION IN BATUR TENGAH VILLAGE, KINTAMANI DISTRICT, BANGLI - Ida Bagus Kesuma Ananda; Ni Nyoman Perni; Gek Diah Desi Sentana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study is motivated by the growth of experience-based tourism in the Kintamani area and the increasing competition among coffee shops, which necessitates the implementation of effective marketing strategies. The research problem focuses on how segmentation, targeting, and positioning are applied by Akasa Specialty Coffee as a tourist attraction. This study aims to analyze and evaluate the marketing strategy of Akasa Specialty Coffee based on the Segmenting, Targeting, and Positioning (STP) approach. This research employs a qualitative descriptive method, with the study conducted at Akasa Specialty Coffee, located in Batur Tengah Village, Kintamani. Data were collected through observation, in-depth interviews with management and tourists, documentation, and literature review. Informants were selected using purposive sampling, and data were analyzed descriptively and interpretatively to understand tourist characteristics and the implementation of marketing strategies. The findings indicate that market segmentation is dominated by productive-age tourists who are experience-oriented, with visitation patterns primarily as a stopover during travel. The targeting strategy applied is selective specialization, aiming at multiple segments simultaneously; however, it has not yet demonstrated a clear focus on the most potential primary segment. The positioning of Akasa Specialty Coffee as an experience-based specialty coffee destination has been established; however, in tourists’ perceptions, the attraction of natural scenery remains more prominent than its identity as a specialty coffee destination. This study concludes that the STP-based marketing strategy has been implemented but is not yet optimal in strengthening differentiation and consistency of experience. Therefore, it is necessary to refine priority segmentation and reinforce experience-based coffee positioning to enhance competitiveness as a tourist attraction. Keywords: Marketing Strategy, Tourist Attraction, Specialty Coffee